2013
DOI: 10.1016/j.jaut.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of X-Linked genes in T cells from women with lupus

Abstract: Women develop lupus more frequently than men and the reason remains incompletely understood. Evidence that men with Klinefelter’s Syndrome (XXY) develop lupus at approximately the same rate as women suggests that a second X chromosome contributes. However, since the second X is normally inactivated, how it predisposes to lupus is unclear. DNA methylation contributes to the silencing of one X chromosome in women, and CD4+ T cell DNA demethylation contributes to the development of lupus-like autoimmunity. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(137 citation statements)
references
References 52 publications
5
132
0
Order By: Relevance
“…The X chromosome encodes many immune-associated genes, including CD40L, CXCR3, OGT, FOXP3, TLR7, TLR8, IL2RG, BTK, and IL9R (79). Overexpression and/or hypomethylation of CD40L, CXCR3, and OGT have been reported in female but not male patients with SLE (77,78).…”
Section: Ifns and Feedback Loops Involving Sex Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The X chromosome encodes many immune-associated genes, including CD40L, CXCR3, OGT, FOXP3, TLR7, TLR8, IL2RG, BTK, and IL9R (79). Overexpression and/or hypomethylation of CD40L, CXCR3, and OGT have been reported in female but not male patients with SLE (77,78).…”
Section: Ifns and Feedback Loops Involving Sex Hormonesmentioning
confidence: 99%
“…As such, males with the XXY karyotype have a risk of developing SLE that is similar to that of the general female population. In addition, several reports suggest that expression of genes from the partially inactive X chromosome can play a role in autoimmunity (77,78). Thus, Turner and Klinefelter syndromes indicate that aberrations in the content of X chromosomes in the host do affect autoimmune disease, although the one-to-one linkage between numbers of X and Y chromosomes and particular diseases is still unclear.…”
Section: Ifns and Feedback Loops Involving Sex Hormonesmentioning
confidence: 99%
“…In one study of an autoimmune disease, Systemic lupus erythematosus (SLE), several X-linked miRNAs were found overexpressed in T cells of female versus male patients 72 . Several of the differentially expressed miRNAs are located within 5000bp of an estrogen response element and, among the predicted targets, was CBL, a negative regulator of T cell receptor activity, which is down-regulated in T cells of the SLE patients 72 .…”
Section: Introduction (Epidemiology)mentioning
confidence: 99%
“…By comparing the mRNA and miRNA expression profiles in experimentally demethylated T cells from women and men as well as in T cells from women and men with lupus, Hewagama et al identified that miR-98, let-7f-2*, miR-188-3p, miR-421 and miR-503 were overexpressed in women relative to men. They also reported that Casitas B-lineage lymphoma (CBL) protein, an E3 ubiquitin-protein ligase, was targeted by miR-98 and miR-188-3p [33]. Their findings supported that CBL downregulation in T cells could alter T cell receptor signalling pathways and thus potentially contribute to lupus pathogenesis.…”
Section: Altered Gene Transcriptionmentioning
confidence: 83%